Screening strategies for quorum sensing inhibitors in combating bacterial infections - Lan Lu; Mingxing Li; Guojuan Yi; Li Liao; Qiang Cheng; Jie Zhu; Bin Zhang; Yingying Wang; Yong Chen; Ming Zeng (Elsevier, 2022)
Interference with quorum sensing (QS) represents an antivirulence strategy with a significant promise for the treatment of bacterial infections and a new approach to restoring antibiotic tolerance. Over the past two decades, a novel series of studies have reported that quorum quenching approaches and the discovery of quorum sensing inhibitors (QSIs) have a strong impact on the discovery of anti-infective drugs against various types of bacteria. The discovery of QSI was demonstrated to be an appropriate strategy to expand the anti-infective therapeutic approaches to complement classical antibiotics and antimicrobial agents. For the discovery of QSIs, diverse approaches exist and develop in-step with the scale of screening as well as specific QS systems. This review highlights the latest findings in strategies and methodologies for QSI screening, involving activity-based screening with bioassays, chemical methods to seek bacterial QS pathways for QSI discovery, virtual screening for QSI screening, and other potential tools for interpreting QS signaling, which are innovative routes for future efforts to discover additional QSIs to combat bacterial infections.